Synthesis and Characterization of Nanocrystalline Aluminophosphate AlPO4-5 Molecular Sieve (Journal of Engineering, 2018)
Nanocrystalline aluminophosphate AlPO4-5 molecular sieves were synthesized by hydrothermal method (HTS). Synthesis parameters like time and temperature of crystallization were investigated. Type of template (R) and ratio of R/P2O5 were studied also. Characterization of the synthesized AlPO4-5 were done by powder X-ray diffraction (XRD), scanning electron microscopy (SEM/EDX), Fourier transform infrared (FTIR), differential scanning calorimetry-thermogravimetry analysis (DSC-TGA), and N2 adsorption-desorption BET analysis. XRD patterns results showed excellent crystallinity for two types of templates, di-n-propylamine (DPA) and tetrapropyl ammonium hydroxide (TPAOH) for alumminophosphate five (AFI) structure. Nano-level for particle size of 66 nm was revealed by AFM test. Good thermal stability was obtained in DSC-TGA results. Best time and temperature of crystallization of 24h and 190 O C were got. Optimum R/P2O5 for two kind of template was established.